Stigma towards health care providers taking care of COVID-19 patients: A multi-country study - Abdulqadir J. Nashwan (11659453) (2022)
Background Health care providers (HCPs) have always been a common target of stigmatization during widespread infections and COVID-19 is not an exception. Aim This study aims to investigate the prevalence of stigmatization during the COVID-19 pandemic among HCPs in seven different countries using the Stigma COVID-19 Healthcare Providers tool (S19-HCPs). Design Cross-sectional. Methods The S19-HCPs is a self-administered online survey (16-item) developed and validated by the research team. The participants were invited to complete an online survey. Data collection started from June–July 2020 using a convenience sample of HCPs from Iraq, Jordan, Egypt, Saudi Arabia, Indonesia, Philippines, and Kuwait. Results A total number of 1726 participants were included in the final analysis. The majority of the study participants were Jordanians (22%), followed by Kuwaitis (19%), Filipinos (18%) and the lowest participants were Indonesians (6%). Other nationalities were Iraqis, Saudis, and Egyptians with 15%, 11% and 9% respectively. Among the respondents, 57% have worked either in a COVID-19 designated facility or in a quarantine center and 78% claimed that they had received training for COVID-19. Statistical significance between COVID-19 stigma and demographic variables were found in all aspect of the S19-HCPs. Conclusion The findings of this study demonstrated high levels of stigmatization against HCPs in all the included seven countries. On the other hand, they are still perceived positively by their communities and in their utmost, highly motivated to care for COVID-19 patients. Educational and awareness programs could have a crucial role in the solution of stigmatization problems over the world. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2022.e09300